Salivary Glands Proteins Expression of Anopheles dirus A Fed on Plasmodium vivax- and Plasmodium falciparum-Infected Human Blood - Saowanee Cotama; Paron Dekumyoy; Yudthana Samung; Usa Lek-Uthai (Journal of Parasitology Research)
Mosquitoes are able to adapt to feed on blood by the salivary glands which created a protein that works against the haemostasis process. This study aims to investigate the salivary glands proteins expression of 50 adult female An. dirus A mosquitoes, a main vector of malaria in Thailand, each group with an age of 5 days which were artificial membrane fed on sugar, normal blood, blood infected with P. vivax, and blood infected with P. falciparum. Then mosquito salivary gland proteins were analyzed by SDS-PAGE on days 0, 1, 2, 3, and 4 after feeding. The findings revealed that the major salivary glands proteins had molecular weights of 62, 58, 43, 36, 33, 30, and 18 kDa. One protein band of approximately 13 kDa was found in normal blood and blood infected with P. vivax fed on day 0. A stronger protein band, 65 kDa, was expressed from the salivary glands of mosquitoes fed with P. vivax- or P. falciparum-infected blood on only day 0, but none on days 1 to 4. The study shows that salivary glands proteins expression of An. dirus may affect the malaria parasite life cycle and the ability of mosquitoes to transmit malaria parasites in post-24-hour disappearance observation.